Awareness of Pakistani Pregnant Women Regarding Danger Signs of Pregnancy: Awareness of Pregnant Women Regarding Danger Signs of Pregnancy - Bibi, Afsha; Khan, Rasheed Ahmad; Illahi, Noor; Ahmad, Ashfaq; Siani, Mai (Pakistan Journal of Health Sciences, 2023)
The early warning signs of pregnancy suggest that a woman may be dealing with a problem that could endanger her and her unborn child's health. If these warning symptoms are not addressed immediately, the consequences could be severe and even fatal. Objective: To assess Pakistani pregnant women's awareness regarding the danger signs of pregnancy. Methods: This cross-sectional study was conducted at a tertiary care hospital in Karachi among 114 pregnant women from September to December 2022. Participants were recruited through the purposive sample method. Results: According to the study results, 18% of the participants had a low level of awareness, 62% had a moderate, and 20% had a high level of awareness regarding danger signs of pregnancy. Conclusions: This study concluded that most participants had moderate awareness regarding the danger signs of pregnancy. Moreover, there is a need for continued efforts to educate pregnant women about the danger signs of pregnancy to improve their understanding.